Comparison of satisfaction with residential components between previous and current unplanned neighbourhoods among young households in Kano, Nigeria - Abdu, Ado; Hashim, Ahmad Hariza; Abu Samah, Asnarulkhadi; Syed Salim, Azizah Salim (International Institute for Science, Technology & Education, 2014)
Studies on residential satisfaction in unplanned neighbourhoods have focused on social interactions and overall satisfaction with housing and neighbourhood as well as the decision to move. Few studies have focused on the comparison of satisfaction with residential components between previous and current unplanned neighbourhoods. This study compares satisfaction with residential components between previous and current unplanned neighbourhoods among young households in Kano Metropolitan, Nigeria with a view to provide a database to the policy makers on the housing situations in unplanned neighbourhoods. Data for this study was obtained from 364 randomly selected heads of young households in unplanned neighbourhoods in Kano city using self-administered questionnaire survey. Yeh’s Index of satisfaction (YIS) was used in the data analyses to compare the level of satisfaction with residential components (housing and neighbourhood) between the previous and current neighbourhoods among the respondents. The findings showed that there were differences in satisfaction with the components the previous and current unplanned neighbourhoods. The findings further revealed that the respondents were very highly satisfied with current housing features and housing conditions, while moderately satisfied with neighbourhood amenities and accessibility in the current neighbourhoods. However, the respondents were dissatisfied with all the residential components in the previous neighbourhoods. Thus, the respondents were most satisfied with housing and neighbourhood components in the current than in the previous neighbourhoods. It is recommended that policy makers and urban and housing planners should pay more attention to the aspects of residential components that the young households were not highly satisfied with in future policy for improving residential situation of households living in unplanned areas in major cities.